The Results of Experiments the Width of the Soil Deeper Like Crushing Angle and Its Impact on Studying Performance - U.I., Khasanov; A.A, Savriddinov; K.S., Sobirov (RA Journal of Applied Research, 2021)
This article presents the results of experiments on the improvement of the plow, equipped with compacted soil plows in the main tillage, in particular, the loosening of the subsoil with plowing, and the effect of the crushing angle of the soil compactor on its performance.